2009
DOI: 10.1038/nature08182
|View full text |Cite
|
Sign up to set email alerts
|

Origins and evolutionary genomics of the 2009 swine-origin H1N1 influenza A epidemic

Abstract: In March and early April 2009, a new swine-origin influenza A (H1N1) virus (S-OIV) emerged in Mexico and the United States. During the first few weeks of surveillance, the virus spread worldwide to 30 countries (as of May 11) by human-to-human transmission, causing the World Health Organization to raise its pandemic alert to level 5 of 6. This virus has the potential to develop into the first influenza pandemic of the twenty-first century. Here we use evolutionary analysis to estimate the timescale of the orig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

61
1,760
5
18

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 1,947 publications
(1,844 citation statements)
references
References 25 publications
61
1,760
5
18
Order By: Relevance
“…Several analyses have shown that the new pandemic H1N1 (2009) virus in domestic pigs emerged from genetic elements of the old human H1N1 and H3N2 viruses as well as from North American and European porcine H1N1 viruses, probably as ''reassortment'' of successive double infection. These results actualize what the influenza virologist has long feared: not birds (avian influenza) but rather mammals, such as swine, represent, as in the past (H2N2, H3N3), the greatest threat for spreading zooanthroponotic influenza infections to humans [2].…”
supporting
confidence: 55%
“…Several analyses have shown that the new pandemic H1N1 (2009) virus in domestic pigs emerged from genetic elements of the old human H1N1 and H3N2 viruses as well as from North American and European porcine H1N1 viruses, probably as ''reassortment'' of successive double infection. These results actualize what the influenza virologist has long feared: not birds (avian influenza) but rather mammals, such as swine, represent, as in the past (H2N2, H3N3), the greatest threat for spreading zooanthroponotic influenza infections to humans [2].…”
supporting
confidence: 55%
“…During 1998–2009, reassortment of influenza viruses in US pigs occurred relatively frequently ( 37 ). The genotypes of the viruses generated through these reassortments typically contained different swine or human influenza virus HA and NA genes in combination with the TRIG cassette ( 13 – 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Smith et al . [29] showed that virus from the H2N2/1957 and H3N2/1968 pandemics seemed to have originated from avian hosts, probably in Asia. Wild relatives may represent a host population where the virus can evolve and where control measures such as vaccination are not possible to use.…”
Section: Discussionmentioning
confidence: 99%